Human resource development theory and practice - Gold, Jeffrey; Holden, Rich; Iles, Paul (Palgrave Macmillan, 2010)
"This book is a comprehensive and critical evaluation of the theory and practice of HRD. Ideally suited for undergraduates, it guides students through key contemporary topics. Written by a team of leading academic experts and packed with learning activities and real world examples, it is essential reading for any student studying HRD"--Provided by publisher.